PENGARUH STRATEGI THE POWER OF TWO PADA PENDIDIKAN KEWARGANEGARAAN TERHADAP HASIL BELAJAR PESERTA DIDIK SD - Mega Puspitasari; Suryani Suryani; Hery kresnadi (Universitas Tanjungpura, 2017)
AbstrackThis study aimed to analyze the effect of using the power of two strategy in learning civic education towards students outcome of the fifth grade of elementary schools in Pontianak subdistrict. The method used is experiment with the form of quasi experimental design. The population in this study is the entire fifth grade of elementary schools in Pontianak subditrict with special criteria, consisted of 431 people. Based on data analysis obtained average yield post-test student 74,67. Based on the analysis of hypothesis testing using t-test is obtained = 3,10 was obtained = 1,997, which means t_hitung (3,10)> t table (1,997), so Ha is received. So we can conclude that there is an influence on the implementation of the power of two strategy in learning civic education towards students outcome of the fifth grade of elementary schools in Pontianak subdistrict. Keywords: The Power Of Two, Civic Education Learning